The Road to Self-Leadership: Teachers’ Mindful Awareness, Engaging Leadership, Commitment, Work Engagement, and Need Satisfaction - Valenzuela, Victoria Pena; Daez, Francisco DP. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The purpose of the study is to examine which of the following var-iables: mindful awareness, engaging leadership, and commitment of women teachers significantly influence work engagement and basic needs satisfaction. The study employed the descriptive-correlational research design and N=273 was purposively selected teachers enrolled in the Graduate School of Meycauayan College, Bulacan, Philippines. Mean, weighted mean, Pearson r, and multi-ple linear regression are the statistical tools used in analyzing and interpreting the data. Findings reveal a significant relationship between mindfulness awareness, engaging leadership, and com-mitment to work engagement and basic needs satisfaction of fe-male teachers, The study was able to determine that commitment predicts the teachers' work engagement and basic needs satisfac-tion. Implications for professional development that boost self-leadership and mindfulness training programs are integrated into teachers’ wellness policies to ensure their work engagement and satisfy their basic needs.